Free-to-play mobile video games, bias, and norms - Paul, Christopher A. (The MIT Press, 2020)
"Paul charts the appeal of free-to-play games and examines how they challenge dominant game industry norms"--
Keywords: Videospielemarkt; Mobiles Endgerät; Video games / Economic aspects; Video games industry